Harry Britt and Phillip Burton - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows group portrait of (left-to-right) two unidentified men, San Francisco Supersivor Harrry Britt and Congressman Phillip Burton from California at the National March on Washington for Lesbian and Gay Rights.